Peran Badan Permusyawaratan Desa (BPD) dalam Meningkatkan Partisipasi Masyarakat Melalui Penyaluran Aspirasi dalam Perencanaan Pembangunan di Desa Medan Estate - Dewi Romantika Tinambunan; Jahya Adiputra Simbolon; Putri Widia Ningsih; Julia Ivanna (Badan Penerbit STIEPARI Press, 2025)
This study aims to describe and analyze the role of the Village Consultative Body (BPD) in increasing community participation through channeling aspirations in development planning in Medan Estate Village. As a representative institution of the village community, BPD has a strategic role and function in bridging communication between the government and the community, especially in the process of future village development planning. This study uses a qualitative descriptive method with data collection techniques in the form of observation, interviews, and documentation. The results of the study indicate that BPD in Medan Estate Village has made efforts to accommodate and convey community aspirations. However, there are still several obstacles, such as differences in perception between BPD and the village government, as well as between BPD and the community itself. Nevertheless, BPD continues to carry out its function in exploring, accommodating, managing, and conveying community aspirations as part of efforts to encourage participation in village development.